Digital Literacy's Influence on Critical Thinking Skills of Office Administration Education Students at UNESA - Panduwinata, Lifa; Setiawati, Fadilah (Universitas Nusantara PGRI Kediri, 2024)
This study aims to discover a significant positive relationship between digital literacy and critical thinking abilities among students in the Office Administration Education Program at Universitas Negeri Surabaya. The research employed a quantitative ex-post facto design. The sample consisted of 235 randomly selected students from a population of 650. Sample determination utilized the Isaac and Michael table with a 5% margin of error. Data collection was conducted via survey using a questionnaire. Data analysis techniques included outer model analysis (convergent validity, composite reliability, Cronbach's alpha, discriminant validity, AVE), inner model analysis (R-Square, F-Square, direct effect) using smartPLS 4.0 software. The findings indicate that digital literacy significantly influences critical thinking abilities among Office Administration Education students’ class of 2021-2023. The implications of this research are that a student's digital literacy can aid in collecting, organizing, and analyzing data, as well as synthesizing information from various digital sources, allowing one to build a more comprehensive and integrated understanding of an issue and develop stronger arguments.